Morning blood pressure surge and its relation to insulin resistance in patients of reproductive age with polycystic ovary syndrome - Hasan Kadi; Eyup Avci; Akin Usta; Abdullah Orhan Demirtaş (BMC, 2018)
Abstract Background Our aim in this study was to investigate morning blood pressure surge (MBPS) in patients of reproductive age with polycystic ovary syndrome (PCOS) and its relation to insulin resistance (IR). Methods Fifty-three patients with PCOS without additional illness were included in the study. Forty-two age-matched subjects without PCOS were selected as the control group. All study subjects underwent 24-h blood pressure monitoring. Patients with additional illnesses, drug users, smokers, and alcohol and drug abusers were excluded. Blood insulin, fasting glucose, lipid profile, and hormone profile were measured. Insulin resistance was calculated using the HOMA-IR formula. Results Median age (years) was 27 (20-33) in the PCOS group and 27 (22-33) in the control group. Body mass index was higher in the PCOS group. Office systolic and diastolic blood pressure was higher in the PCOS group. Mean awakening 2-h BPs (mmHg) was 110 ± 7 in the control group and 118 ± 5 in the PCOS group (p < 0.001). Mean MBPS (mmHg) was 21 ± 6 in the control group and 29 ± 8 in the PCOS group. Mean MBPS was higher in the PCOS group (p < 0.001). IR was more frequent in the PCOS group. Based on logistic regression analysis, the presence of PCOS and IR were independent predictors for MBPS. Conclusions The results of our study showed that MBPS increased excessively when compared to non-PCOS controls in young women with PCOS during reproductive age. In addition, PCOS and insulin resistance were independent risk factors for exaggerated MBPS.